2006
DOI: 10.1038/oby.2006.264
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Status and Weight‐Related Distress in Overweight or At‐Risk‐for‐Overweight Children

Abstract: Research Methods and Procedures:We associated selfreport of depression, trait anxiety, and weight-related distress (body size dissatisfaction and weight-related peer teasing after controlling for the effects of weight) in 164 children (black 35%; age 11.9 Ϯ 2.5 years; girls 51%) who were overweight or at-high-risk-for-overweight and were not seeking weight loss. Results: Overall, heavier children reported more psychological and weight-related distress. Black children reported more anxiety and body size dissati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
104
2
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 42 publications
11
104
2
2
Order By: Relevance
“…Similar to the American-based studies, we found that the experience of weight-based teasing is prevalent, especially among those who are overweight or obese. In both normal weight and overweight classifications, girls reported higher prevalences of weight-based teasing than boys -a sex difference that has been reported in American studies (7,8).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Similar to the American-based studies, we found that the experience of weight-based teasing is prevalent, especially among those who are overweight or obese. In both normal weight and overweight classifications, girls reported higher prevalences of weight-based teasing than boys -a sex difference that has been reported in American studies (7,8).…”
Section: Resultsmentioning
confidence: 61%
“…As expected, weight-based teasing occurs more often in overweight children and youth than in their normal weight peers (5)(6)(7)(8)(9). Much of the literature on weight-based teasing has shown untoward effects on body dissatisfaction, selfesteem and disordered eating, including bulimic eating behaviour (6,10,11).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This association might be explained by decreased physical activity, increased appetite associated with depression, or weight gain associated with side effects of medications used to treat depression (Stunkard et al 2003;Patten et al 2009;Hasnain et al 2012). Conversely, obesity may increase the risk for depression, possibly mediated by body shape dissatisfaction, peer or parental teasing, and decreased self-esteem, or because of incipient metabolic syndrome (Young-Hyman et al 2006;Libbey et al 2008;Wang et al 2009;Bang et al 2012;Hamer et al 2012;SanchezVillegas et al 2013). However, some longitudinal studies do not find that obesity predicts future depression (Gariepy et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the USA approximately one in six children between the ages of 2 and 19 years is obese and approximately one in three children is overweight (5) . A number of negative physical health consequences (6) and psychosocial consequences (7,8) of childhood overweight and obesity have been well documented. The urgency of this public health problem has led to revisions in terminology such that children with BMI-for-age $95th percentile are designated 'obese' and children with BMIfor-age $85th percentile but ,95th percentile are classified as 'overweight' (9) .…”
mentioning
confidence: 99%